THE INFLUENCE OF PROFESSIONAL COMPETENCIES OF TEACHERS AND EDUCATIONAL PERSONNEL SERVICES ON THE LEARNING MOTIVATION OF STUDENTS IN THE 1-YEAR EDUCATIONAL PROGRAM AT LPP ARIYANTI BANDUNG - Handayani, Fitri; Adriza, Adriza; Wahyuningsih, Sri (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to determine the Influence of Professional Competence of Teachers and Education Personnel Services on the Learning Motivation of Students in the 1-Year Education Program at LPP Ariyanti Bandung. Professional competence of teachers is very important for the high and low learning motivation of students. The research method used in this study is a quantitative research method. The population of this study was 110 Students in the 1-Year Education Program at LPP Ariyanti Bandung, while the sample in this study was 52 Students in the 1-Year Education Program at LPP Ariyanti Bandung. Based on the results of multiple linear regression tests, it can be concluded that professional competence of teachers and education personnel services have an effect on the learning motivation of Students in the 1-Year Education Program at LPP Ariyanti Bandung by 59.7% while the remaining 40.3% is influenced by other variables. And the direction of the relationship between the two variables is positive, so it can be interpreted that the higher the professional competence of teachers, the higher the learning motivation of students. Likewise, the higher the service of education personnel, the higher the learning motivation of students